Social media and e-commerce online shopping perceived risk among micro SMEs in Malaysia / Mohd Remie Mohd Johan, Md Azalanshah Md Syed and Hamedi Mohd Adnan - Mohd Johan, Mohd Remie; Md Syed, Md Azalanshah; Mohd Adnan, Hamedi (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2019)
Online shopping has rapidly grown in a global marketing environment and has attracted people to purchase the product through the social media platform (Facebook & Instagram) and e-commerce. It is made possible for new start-ups, especially micro SMEs to conduct and increase their business activities online considering it is the low-cost marketing (advertising & branding) events. However, social media and e-commerce online shopping have specific risks for the SMEs besides its benefits. Perceived risk among SMEs has been considered as a primary concern of the decision-making process in social media and e-commerce shopping platform. This study aims to observe SMEs' concern on specific perceived risks and to examine the effect of perceived risks (customer preferences, non- delivery risk and financial transaction & security risk) in social media and e-commerce online shopping in Malaysia. Results revealed that customer preferences, non-delivery risk and financial transaction & security risk significantly affect social media and e-commerce online shopping platform usage among micro SMEs in Malaysia. This study has an important implication that provides new start-up business owners with the importance of consumer's risk perception to adopt with adequate risk-reduction strategies in the social media online and e-commerce shopping environment.